1993
DOI: 10.1002/1098-108x(199311)14:3<375::aid-eat2260140316>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of self-induced vomiting and laxative/medication abuse among female adolescents: A longitudinal study

Abstract: In order to assess the prevalence and stability of weight reduction techniques utilized by adolescent females, three comprehensive samples of middle school and high school students (ages 12–18) were surveyed in the springs of 1984, 1989, and 1992. All participants were enrolled in the same school district to ensure that the groups were demographically equivalent. The results demonstrated a significant decrease in the use of appetite suppressants among high school students. However, middle school females report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 6 publications
2
30
1
1
Order By: Relevance
“…Purging behaviors to control weight were again more common among students in Tehran than among students in Pakistan and Cairo (Nasser, 1994). However, Newmark-Sztainer, Palti, andButler (1995) reported higher rates of purging among high school girls in Israel and several studies in the United States have also reported higher rates (Phelps, Andrea, Rizzo, Johnston, & Main, 1993;French et al, 1997). Many of the weight control behaviors practiced by the Tehran students were similar to those used in Western countries.…”
Section: Discussionsupporting
confidence: 85%
“…Purging behaviors to control weight were again more common among students in Tehran than among students in Pakistan and Cairo (Nasser, 1994). However, Newmark-Sztainer, Palti, andButler (1995) reported higher rates of purging among high school girls in Israel and several studies in the United States have also reported higher rates (Phelps, Andrea, Rizzo, Johnston, & Main, 1993;French et al, 1997). Many of the weight control behaviors practiced by the Tehran students were similar to those used in Western countries.…”
Section: Discussionsupporting
confidence: 85%
“…Several investigators have suggested that the diagnostic thresholds defined in the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV-TR; American Psychiatric Association 2000) for anorexia and bulimia are too high and that partialsyndrome cases should be included in studies of eating disorders because they represent a risk to health, as well (Herzog and Delinsky 2001). For example, researchers have investigated factors related to eating disorder symptomology such as dieting and unhealthy weight reduction practices (Phelps et al 1993), unhealthy pursuit of muscularity (McCreary and Sasse 2000; Ricciardelli and McCabe 2004), body dissatisfaction (Presnell et al 2004;Stice and Whitenton 2002), and drive for thinness (Wertheim et al 2002) without including the full-syndrome EDs. In general, research involving non-clinical populations of adolescent girls and adult women has suggested that the prevalence of partial syndromes is higher than full syndrome EDs (Shisslak et al 1995).…”
Section: Review Of Literaturementioning
confidence: 99%
“…This high rate of symptoms is linked both with the questions and concerns raised by the pubertal changes and by the increasing interest of our society in issues such as the shape of the female body and the search for an ideal weight. The prevalence rate of purging behaviors (vomiting, laxatives, diuretics) fluctuates between 5% and 16%, depending on the setting and the age of the adolescent population [50,56,57]. In European countries, the figures are fairly similar [31,42,58 -60].…”
Section: Prevalencementioning
confidence: 99%